2003
DOI: 10.1007/s10353-003-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy of the Human Intrinsic Laryngeal Muscles

Abstract: Background: Since the beginning of the Christian era, numerous reports have dealt with the construction and functional organization of the larynx, thus stressing its role as the keystone of vocalization in vertebrates. The purpose of this review is to provide a comprehensive summary of basic anatomical facts and to point out certain new aspects of the innervation of laryngeal muscles. Methods: The data presented herein were collected from a preliminary gross anatomical study performed in six human individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…The findings obtained from our present and previous studies 20 and others [24][25][26][27][28][29] do not support the now-prevailing view that all the intrinsic laryngeal muscles are innervated by the RLN except the CT muscle, which is innervated by the ESLN. 30 More recently, we reported that the human ESLN supplied branches to the inferior pharyngeal constrictor and upper esophageal sphincter.…”
Section: Distribution Of the Esln And Physiological Implicationscontrasting
confidence: 74%
“…The findings obtained from our present and previous studies 20 and others [24][25][26][27][28][29] do not support the now-prevailing view that all the intrinsic laryngeal muscles are innervated by the RLN except the CT muscle, which is innervated by the ESLN. 30 More recently, we reported that the human ESLN supplied branches to the inferior pharyngeal constrictor and upper esophageal sphincter.…”
Section: Distribution Of the Esln And Physiological Implicationscontrasting
confidence: 74%
“…20,28 Excessive tension of the cricothyroid muscles results in higher than normal longitudinal tension of the vocal folds. 29 The relationship between tension of the vocal folds and F0 of phonation can be likened to the tension of a string and the pitch at which it vibrates; as tension increases, so too does F0. 11 Wolfe et al 5 observed a significant increase in F0 during a 30-minute period of simulated instruction and suggested that this finding may be an acoustic indication of increased laryngeal tension.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the mechanistic basis for this phenomenon and its relation to laryngeal nerve function remains unclear. This issue may be resolved by additional anatomical and neurophysiological studies designed to address this specific question (21,22). Finally, the intraoperative loss of signal is not always associated with a postoperative recurrent nerve dysfunction.…”
Section: Effect Of Anaesthesia On the Electromyogrammentioning
confidence: 94%